iPhone For Seniors - Spivey, Dwight (Hoboken, New Jersey : John Wiley & Sons, Inc., 2020)
Provides instruction for seniors on using the iPhone, including how to make and receive calls, use email and social media, browse the web, play games, listen to music and podcasts, work with reminders and notifications, and read e-books.
Includes index.
Keywords: iPhone (Smartphone).; Smartphones